Significant strengthening of a lithium disilicate glass by Li+/Na+ exchange at substantially lowered temperature. Issue 17 (1st December 2019) - Li, X.C.; Li, D.; Meng, M.; Wei, R.; He, L.; Zhang, S.F.
Abstract: A lithium disilicate (LD) glass with stoichiometric composition and glass transition temperature ( T g ) ∼ 470 °C was ion-exchanged over a wide temperature range below the T g . The ion-exchange temperatures used were 380 °C or 315 °C in a pure molten NaNO3 bath, and 235 °C in a molten mixed salt bath of 50 mol% NaNO3 ＋50 mol% KNO3 . Temperature-dependences of surface layer morphology and mechanical behavior of the ion-exchanged glass were investigated. It was found that similar surface Na + concentrations were presented on the glass after the ion-exchange at all the three temperatures for different times. Surface failure occurred on the glass after the treatments at the two higher temperatures for longer time to increase the ion-exchanged depth. The surface failure could be completely avoid by substantially lowering the temperature to 235 °C in the mixed salt bath for much longer time to obtain a similar level of case depth. Similar strengthening effects were exhibited at the three temperatures as the ion-exchanged depth was shallower. With further increasing the depth, however, much more significantly strengthening effect could be achieved at the substantially lowered temperature. Flexural strength of the glass could be enhanced from ∼ 97 MPa to ∼ 520 MPa after the treatment at 235 °C for 128 h. The temperature-dependent effect to strengthen the LD glass by Li + /Na + exchange was attributed to the combined effect of stress relaxation during ion-exchange and thermal contraction coefficient mismatch between the ion-exchanged surface layer and the internal bulk glass.